Peluang pengembangan produksi perikanan tangkap di wilayah Kabupaten Tegal dan Pekalongan pada masa mendatang: Opportunities for development of capture fishery production in Tegal and Pekalongan Regencies in the future - Ariadi, Heri; Hasan, Reza Adhitama Nugraha; Mujtahidah, Tholibah; Wafi, Abdul (Fakultas Pertanian Universitas Yudharta Pasuruan, 2022)
Introduction: The availability of food sources influences the abundance of insect pollinators. The interaction between plants and insect pollinators is a symbiotic mutualism. In addition, the use of a plant barrier could attract insect pollinators in foraging activities. The study aimed to determine the effect of plant barrier on the abundance of insect pollinators and the yield of chili pepper. This research was carried out on agricultural land in Lumpoknyo village, North Luwuk, Banggai Regency, in July - December 2020. Methods: The research was carried out using a randomized block design, and four treatments, namely chili plants without barriers and covered with nets (P0 or control), eggplant plant barriers (P1), plant barriers with Zinnia sp and Cosmos caudatus (P2), and tomato plant barrier (P3). Observations were made every day at the time of flowering for 14 days. Sample collection of insect pollinators is done by taking insects that visit chili flowers using a sweep net. Results: Three species of insect pollinators were collected, namely Bembecinius sp, Ceratina sp, and Nomia sp. 730 individuals were found on eggplant barriers, 660 individuals on Zinnia sp and Cosmos caudatus barriers and 592 on tomato barriers. The highest individual is Ceratina sp (810 individuals), followed by Nomia sp. (799 individuals), and Bembecinius sp (373 individuals). Chili pepper cultivation using eggplant barrier yielded 4,93 kg/plot, Zinnia sp and Cosmos caudatus barriers 3,96 kg/plot, tomato barrier 3,62 kg/plot, and the lowest yield was shown in chili pepper fields covered with insect nets. of 2,00 kg/plot. Conclusion: The barrier system using eggplant is considered effective for increasing the abundance of insect pollinators and the yield of chili pepper.